The consumption of experiential gifts is construed as more autonomy supportive and leads to greater gratitude, especially when they are given out of love - Puente-Díaz, Rogelio; Cavazos-Arroyo, Judith (Frontiers in Psychology, 2024)
The purpose of this investigation was to examine the indirect influence of recalling the consumption of types of gifts, experiential and material, on gratitude by increasing autonomy support. In addition, we tested the conditional influence of the presumed motives of gift-givers from the perspective of gift recipients based on the postulates of Self-Determination Theory. First, participants were randomly to assigned to one of the following conditions: Consumption-of-experiential gift or consumption-of-material gift conditions. After, participants filled out a battery of questionnaires assessing autonomy support and gratitude. Results showed that the consumption of experiential gifts was construed as more autonomy supportive than the consumption of their material counterparts, which then had a positive relationship with gratitude. In experiment two, we tested the proposed mediator, autonomy support, by asking participants to either recall the consumption of the gift that was consistent with their true values or the consumption of an ordinary gift and completed a set of questions assessing autonomy support and gratitude. Results showed that recalling a gift consistent with consumers’ true values led to higher levels of autonomy support than recalling an ordinary gift, which was then positively correlated with gratitude. In the third experiment, we conducted a conceptual replication of experiment one and added the examination of the presumed motives of gift-givers as a potential moderator. Results replicated the significant mediation effect found in study 1 and showed that the conditional indirect effect was stronger when gift recipients attributed integrated motives to the gift-givers. The findings were discussed. .